Update on the Relationship Between Depression and Neuroendocrine Metabolism - Qiu, Wenxin; Cai, Xiaodan; Zheng, Chenhui; Qiu, Shumin; Ke, Hanyang; Huang, Yinqiong (Frontiers in Neuroscience, 2021)
Through the past decade of research, the correlation between depression and metabolic diseases has been noticed. More and more studies have confirmed that depression is comorbid with a variety of metabolic diseases, such as obesity, diabetes, metabolic syndrome and so on. Studies showed that the underlying mechanisms of both depression and metabolic diseases include chronic inflammatory state, which is significantly related to the severity. In addition, they also involve endocrine, immune systems. At present, the effects of clinical treatments of depression is limited. Therefore, exploring the co-disease mechanism of depression and metabolic diseases is helpful to find a new clinical therapeutic intervention strategy. Herein, focusing on the relationship between depression and metabolic diseases, this manuscript aims to provide an overview of the comorbidity of depression and metabolic.